Endotoxin Adsorption Therapy for Septic Shock Using Polymyxin B-Immobilized Fibers (PMX): Evaluation by High-sensitivity Endotoxin Assay and Measurement of the Cytokine Production Capacity - Kojika, Masahiro; Sato, Nobuhiro; Yaegashi, Yasunori; Suzuki, Yasusi; Suzuki, Kenji; Nakae, Hajime; Endo, Sigeatu (Therapeutic apheresis and dialysis, 2006)
:  Because of its low sensitivity, the conventional measurement method for endotoxin (ET) is not the most appropriate for monitoring the effect of ET adsorption therapy. Thus, the efficacy of ET adsorption therapy was investigated using a newly developed high‐sensitivity ET assay method. The changes in the cytokine production capacity of whole blood were also examined. We treated 24 peritonitis patients who had developed postoperative septic shock with ET adsorption therapy using a column of polymyxin B‐immobilized fibers (PMX) and their serum ET levels were measured using the high‐sensitivity ET assay based on the kinetic turbidimetric Limulus assay. In addition, the changes in the tumor necrosis factor‐(TNF‐α) production capacity of whole blood following lipopolysaccharide (LPS) stimulation and clinical outcome in the study patients were also examined. The 28‐day mortality rate was 12%. PMX‐direct hemoperfusion (PMX‐DHP) was associated with elevation of the mean arterial pressure and urine output, reduction in the mean dose requirement of vasopressor agents, and recovery from the shock state in all the patients. The PaO2/FIO2 ratio also showed significant improvement. Using the high‐sensitivity ET assay, ET was detected in the blood of 20 out of the 24 patients (80%) before the PMX‐DHP, and a significant reduction in the ET level was noted after the PMX‐DHP. The TNF‐α production capacity of whole blood, which was found to be lower in the septic shock patients than in healthy subjects, was significantly increased after PMX‐DHP. Elimination of ET by PMX‐DHP in septic shock patients was confirmed by the high‐sensitivity ET assay. PMX‐DHP is thus considered to be a useful adjuvant therapeutic technique in the treatment of septic shock. Also, PMX‐DHP might alleviate the immunosuppression associated with severe sepsis.